(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
In the last two decades, United Nations peace operations have become one of the most common mechanisms used by the Security Council in humanitarian emergencies in armed conflict. Data and practical analysis confirm the increasing number of missions based on Chapter VII of the United Nations Charter, which, far from being exceptional cases, require a far more explicit legal framework than the one we have today, which is still conditioned by the institution’s traditional set-up.